EFFECT OF SCALE, PROPORTION, AND WALKABILITY TO VISUAL TROTOAR QUALITY UNDER THE TERAS CIHAMPELAS - Tekadtuera (Jurnal Riset Arsitektur, 2018)
Abstract- The introduction the new infrastructures in the city of Bandung is being executed in order to tackle various urban problems, such as the lack of pedestrian-friendly spacse and the lack of public spaces throughout the city. In 2017, the Local Government of Bandung opened Teras Cihampelas, which is a skywalk-type of infrastructure that was built above Cihampelas Street in order to relocate the street vendors that had been occupying the pedestrianway in Jalan Cihampelas and to become a new public space. The new structure, in fact, affects the scale and proportion of the spaces between buildings along the road and reconfigurated the visual qualities of the existing street. Therefore, the visual experiences in the pedestrianway throughout Cihampelas Street had also affected by the changes of those factors.The method used in this research is a qualitative triangulation method which can be done by mapping the typology of the space between buildings based on the existing buildings’ intensity for further analysis which consist of scale and proportion analysis, and walkability analysis that was based on visual evaluation. The analysis of each typology will then be mapped and merged in each pedestrianways to provide the visual experiences of the pedestrian in Cihampelas Street.The visual quality in Cihampelas Street appears to slightly exceed the minimum comfortability standard but still far from the maximum comfort for a pedestrianway. This problem appears because there are lacks of legibility and imageability that the pedestrian can grasp in most parts of the pedestrianway. But aside from those factors, other factors like transparency, complexity, and coherence in Cihampelas Street are highly achieved so that the pedestrianway can still be comfortably walkable by the pedestrians Key Words: scale, proportion, visual quality, walkabillity, visual experience, pedestrian, qualitative triangulation method, Cihampelas Street